2020
DOI: 10.1021/acs.est.0c02299
|View full text |Cite
|
Sign up to set email alerts
|

Diet Shifts Explain Temporal Trends of Pollutant Levels in Indo-Pacific Humpback Dolphins (Sousa chinensis) from the Pearl River Estuary, China

Abstract: We examined spatiotemporal trends of diet compositions and their relationship with pollutant accumulation levels in 46 weaning Indo-Pacific humpback dolphins (n = 46) from 2004 to 2017 in the Pearl River Estuary (PRE) based on blubber fatty acid signatures using quantitative fatty acid signature analysis in R (QFASAR). Fifty-one potential prey species were tested, among which 13 had a mean relative proportion greater than 1% in dolphin diets. Bombay duck was the predominant prey species, followed by Dussumier’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 64 publications
4
19
0
Order By: Relevance
“…The eleven-year temporal trends in cortisol levels were similar to those of diet shifts and pollutant accumulation burdens in dolphins in recent years. Considering that diet and contaminants are stressors, we hypothesized that the diet proportion and contaminant level contributed to the cortisol level. Combined with our previously reported diet compositions of S.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The eleven-year temporal trends in cortisol levels were similar to those of diet shifts and pollutant accumulation burdens in dolphins in recent years. Considering that diet and contaminants are stressors, we hypothesized that the diet proportion and contaminant level contributed to the cortisol level. Combined with our previously reported diet compositions of S.…”
Section: Resultsmentioning
confidence: 73%
“…The high body burden of contaminants in marine mammals has been associated with the endocrine and immune system disruption in previous research studies. , Therefore, we hypothesized that the significantly decreased body burdens of contaminants, for example, dichlorodiphenyltrichloroethanes (DDTs), perfluorooctanesulfonate (PFOS), and chromium (Cr) in the PRE dolphins in recent years may have contributed to the reduced blubber cortisol levels in these animals. We also revealed that diet changes from large, demersal, and high trophic level fishes to small, pelagic, and low trophic level fishes because of environmental changes, which is supposed to cause high stress for the dolphins to catch more fishes, may have contributed to elevated cortisol levels. In this study, we evaluated the endocrine response (levels of blubber cortisol) in relation to two primary stressors: (1) exposure to high-level contaminants and (2) significant diet change, as indicated by contaminant exposure levels or diet compositions correlated positively or negatively with the blubber cortisol content, respectively.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although the observed BMFs were based on highly variable concentrations of POPs in a limited number of samples in a field study, more reliable BMFs were acquired based on QFASA results than BMFs with unknown diet compositions of predators. QFASA has been increasingly used to study marine food webs in the last two decades. The present study suggests that QFASA is a promising tool to trace credible prey/predator relationships in terrestrial environments, which will largely extend knowledge on the trophic transfer of essential nutrients and contaminants in riparian and terrestrial food webs.…”
Section: Discussionmentioning
confidence: 84%
“…Quantitative fatty acid signature analysis (QFASA) is a promising method to investigate the diet compositions of wildlife. , Fatty acids are recalcitrant during digestion and distribution in vertebrates and can be conservatively transferred to higher trophic levels, , potentially reflecting the diet sources of vertebrates. QFASAR (using R for QFASA) has been increasingly applied in marine organisms such as marine mammals , and fish , to achieve quantitative diet compositions but has not yet been reported in terrestrial and riparian food chains.…”
Section: Introductionmentioning
confidence: 99%